Handbook of effective inclusive elementary schools : research and practice - McLeskey, James, 1949-; Waldron, Nancy L.; Spooner, Fred; Algozzine, Robert (London : Routledge, 2021)
Now in its Second Edition, this seminal handbook offers a comprehensive exploration of how students with disabilities might be provided classrooms and schools that are both inclusive and effective. With an enhanced focus on the elementary level, this new edition provides readers with a richer, more holistic understanding of how inclusive settings operate in K-5, featuring expanded chapters on principal engagement, teacher preparation, district-level support, school-based improvement practices, and more. Fully revised and updated to reflect changes in the field, each chapter synthesizes the research, explores if and how this knowledge is currently used in schools, and addresses the implications for practice and directions for future research.
Keywords: Inclusive education -- United States; Special education -- United States; Education, Elementary -- United States; Children with disabilities -- Education (Elementary) -- United States; Mainstreaming in education -- United States; EDUCATION / Special Education / General; EDUCATION / Counseling / General; PSYCHOLOGY / Developmental / Adolescent